Financialisation and income inequality: An investigation of the financial Kuznets curve hypothesis among developed and developing countries - Ibrahim N. Khatatbeh; Imad A. Moosa (Heliyon, 2023)
The Financial Kuznets Curve (FKC) is a variant of the renowned Kuznets Curve and a counterpart to the Environmental Kuznets Curve. In this paper, we examine the financial Kuznets curve hypothesis—based on annual data for 20 developed and developing countries—using the Phillips and Hansen (1990) fully modified ordinary least square (FMOLS) and the unobserved components model (UCM). The results correspond to the current divergence in the empirical literature and show support for the inverted U-shaped curve as well as the U-shaped curve, in more than half of the sample countries. The estimated turning points differ significantly across countries and depending on the measure of financialisation used. Overall, the findings of this research suggest that there is no uniform effect of financialisation on income inequality. The results vary according to the level of economic development, financial structure, and potentially other factors that have not been considered in the empirical analysis provided in this paper.